Studying Some Standards of Groundwater Quality and the Water Environment for Different Areas in Diyala Governorate: Mempelajari Beberapa Standar Kualitas Air Tanah dan Lingkungan Air untuk Berbagai Daerah di Kegubernuran Diyala - Salih Saood Yagoub (Universitas Muhammadiyah Sidoarjo, 2024)
In the Diyla area, fourteen ground water samples were obtained for this study in high density polyethylene (HDPE) bottles that had been previously cleaned and filled with diluted HNO3. To prevent cross-contamination, the bottles were rinsed with the same water that would be used for the sample. Using normal procedures, each sample was examined for five parameters: pH, EC, TH, Alkalinity, and F (APHA, 1995). A digital pH metre (Model 802 Systronics) was used in the field to measure pH, and a conductivity metre (Model 304 Systronics) was used to assess EC. The Trimble Juno 3D Handheld is used to help collect the geographic locations of the sample points (EC). Using regular EDTA, a titrimetric analysis of total hardness was conducted. Titrimetric analysis of alkalinity was performed with standard H2SO4. Highlight: Samples collected in HDPE bottles pre-rinsed with sample water. pH, EC, TH, Alkalinity, F analyzed using APHA standards (1995). pH, EC measured in field; hardness, alkalinity by titration. Keywords: Word, Ground Water, Diyala City, Quality Parameters, Ph Metre, Alkalinity